Abu Ali ibn Sina and Medicine - Bozorov Quvonchbek Dilmurod o’g’li; PanjiyevJamshid Tohir o’g’li; Xolboyev Jo`rabek Lutfullo o`g`li (Zien Journals, 2021)
We know that the life of Abu Ali Ibn Sina, a genius scholar of the Eastern world, was as difficult as that of other Eastern thinkers. In the early years of his career, he lost his father, who was his breadwinner. He was also forced to move to Urgench after his activities at the Samanid palace came under threat. Due to the turmoil of his time, the scholar was forced to continue his scientific work in cities such as Ray, Hamadon and Jurjun. Ibn Sina tries to deal with many fields of science to the best of his ability. His book "Al-Qanun fit-tib" was the most important medical manual of its time. Even today, many developed countries are using this book to develop their medical field.
Keywords: Avicenite; Metaphysics; Qarakhanids; Ray